IMPLEMENTASI SUPERVISI KEPALA RUANGAN DALAM MENINGKATKAN FUNGSI PENGARAHAN - Cahya Kinanti, Adelia; Elasari, Yunina; Yeni Wulandari, Rizki (Stikes Yarsi Mataram, 2025)
has been carried out but is not yet optimal due to the lack of a schedule and standard operating procedures (SOP) for supervision. Supervision activities are incidental according to needs and have not been carried out in a structured and well-documented manner. The aim of this research is to determine the implementation of head of room supervision in improving the directing function.The methods used were interviews, documentation studies and observations. It was found that the nursing management problem found was that the implementation of supervision activities was not optimal. The plan that will be carried out is education regarding supervision with the target activity being the head of the room and the executive nurse in the siger room at RSD Dr. A. Dadi Tjokrodipo Bandar Lampung. Implementation was carried out on April 3 2024 with the results that understanding of nursing supervision in the Siger room had increased as evidenced by the results of the pre-test 60-75 and post test 85-95. Therefore, it is hoped that the head of the nursing department, head of the room, and all nurses in the Siger room are committed to carrying out nursing supervision consistently and continuously so that they can identify and overcome problems that hinder nursing actions and find solutions together with the nursing staff.